Pengaruh Platform Pembelajaran Berbasis Digital (EduMu) dan Pengetahuan Teknologi Informasi Terhadap Hasil Belajar Mata Pelajaran Pendidikan Agama Islam pada Siswa SMA Muhammadiyah 4 Kota Bengkulu - Eza Qurnia Hayati (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2023)
This research aims to measure the influence of the Digital Based Learning Platform (eduMu) and Information Technology Knowledge on the learning outcomes of Islamic Religious Education subjects in Muhammadiyah 4 High School students in Bengkulu City. The specific objectives of this research are: (1) Measuring the influence of using the eduMu Platform and Information Technology Knowledge on student learning outcomes, (2) Measuring the influence of Using the eduMu Platform on student learning outcomes, and (3) Measuring the influence of Information Technology Knowledge on learning outcomes student. This type of research is field research, where the researcher is directly involved in collecting data from the population of students in classes X, XI, and XII at SMA Muhammadiyah 4 Bengkulu City. Samples were taken purposively and randomly proportionally. The research results show that: (1) Taken together, the use of the eduMu digital platform and Information Technology Knowledge has a significant and positive effect on student learning motivation, (2) Taken together, the use of the eduMu digital platform and Information Technology Knowledge has no significant effect on student learning outcomes. The implications of this research indicate that to increase motivation to learn Islamic Religious Education, it is necessary to increase the use of the eduMu digital learning platform and knowledge of Information Technology among students.